Pharmacogenetic interactions between antiretroviral drugs and vaginally administered hormonal contraceptives. Issue 3 (April 2020) - Haas, David W.; Cramer, Yoninah S.; Godfrey, Catherine; Rosenkranz, Susan L.; Aweeka, Francesca; Berzins, Baiba; Coombs, Robert; Coughlin, Kristine; Moran, Laura E.; Gingrich, David; Zorrilla, Carmen D.; Baker, Paxton; et al.
Abstract : Objective: In AIDS Clinical Trials Group study A5316, efavirenz lowered plasma concentrations of etonogestrel and ethinyl estradiol, given as a vaginal ring, while atazanavir/ritonavir increased etonogestrel and lowered ethinyl estradiol concentrations. We characterized the pharmacogenetics of these interactions. Methods: In A5316, women with HIV enrolled into control (no antiretrovirals), efavirenz [600 mg daily with nucleoside/nucleotide reverse transcriptase inhibitors (NRTIs)], and atazanavir/ritonavir (300/100 mg daily with NRTIs) groups. On day 0, a vaginal ring was inserted, releasing etonogestrel/ethinyl estradiol 120/15 μg/day. Intensive plasma sampling for antiretrovirals was obtained on days 0 and 21, and single samples for etonogestrel and ethinyl estradiol on days 7, 14, and 21. Seventeen genetic polymorphisms were analyzed. Results: The 72 participants in this analysis included 25, 24 and 23 in the control, efavirenz, and atazanavir/ritonavir groups, respectively. At day 21 in the efavirenz group, CYP2B6 genotype was associated with increased plasma efavirenz exposure ( P  = 3.2 × 10 −3 ), decreased plasma concentrations of etonogestrel ( P  = 1.7 × 10 −3 ), and decreased ethinyl estradiol ( P  = 6.7 × 10 −4 ). Compared to controls, efavirenz reduced median etonogestrel concentrations by at least 93% in CYP2B6 slow metabolizers versus approximately 75% in normal and intermediate metabolizers. Efavirenz reduced median ethinyl estradiol concentrations by 75% in CYP2B6 slow metabolizers versus approximately 41% in normal and intermediate metabolizers. Conclusion: CYP2B6 slow metabolizer genotype worsens the pharmacokinetic interaction of efavirenz with hormonal contraceptives administered by vaginal ring. Efavirenz dose reduction in CYP2B6 slow metabolizers may reduce, but will likely not eliminate, this interaction. Abstract : Supplemental Digital Content is available in the text.